Enteric Duplication Cyst Associated With Meckel's Diverticulum: A Rare Cause of Acute Abdomen - Kugendran Ponniah MD; Stephen Kinsey-Trotman BMBS; Naveen Agarwal MD; Dandie Lachlan BMBS; Matthew Kozman MBBS, BPharm, MS, FRACS, CSSANZ (SAGE Publishing, 2024)
We report a case of a 26-year-old type 1 diabetic woman presenting with acute lower abdominal pain, bloating, and vomiting. Initial examination revealed right lower quadrant tenderness and a suprapubic mass. Computed tomography (CT) imaging identified a 12-cm cystic structure suggestive of a dilated bowel loop with an adjacent inflamed 7-cm small bowel segment. Surgical exploration uncovered a Merkel's diverticulum-associated duplication cyst originating from the Meckel's diverticulum. Subsequent complications included an anastomotic leak, requiring relook laparotomy and the formation of a double-barrel stoma. The patient recovered and was discharged on day 13. This case highlights the diagnostic challenge of Meckel's diverticulum-associated duplication cysts, emphasizing the need for vigilance in managing complex abdominal presentations.